Pengaruh Ketersediaan Infrastruktur terhadap Aktivitas-aktivitas Logistik di Kecamatan Gantung Kabupaten Belitung Timur - Dedeh Maryani (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
This study aims to determine: the condition of logistics transportation transportation, logistics activities in meeting the needs of the community and how much influence the availability of transportation has on logistics activities in Gantung District, East Belitung Regency. The method used is a mixed method (mix method), namely sequential exploratory strategy (quality-quan-quan interpretation). The results of this study that the availability of infrastructure obtained an average answer score on each item ranging on a scale between 4-5, namely the lowest on item X5 (transportation manager) = 4.16 and the highest on item X3 (vehicle as a tool) = 4.38 with a standard deviation between 0.050 – 0.82. Meanwhile, the lowest logistical activities were at item Y4 (material handling) = 3.98 and the highest was item Y3 (communication in logistics) = 4.40 with standard deviation = 0.532-0.711. The results of the hypothesis test show that there is an influence of Infrastructure on Logistics at a significance level of 0.05. The coefficient of determination (R Square) = 0.784, meaning that Logistics Activities can be explained by Infrastructure Availability = 0.784 (78.4%), the remaining 21.6% is explained by other factors not examined. The regression equation is: Y = 10.057 + 0.967 X. a = 10.057 means that if there is no adequate infrastructure then the amount of logistics fulfillment is 10.057 and b = 0.967, it means that if there is an increase in infrastructure by 1 unit, then logistics will increase by 0.967 units and vice versa.